Prediksi Jumlah Produksi Sablon Tahun Menggunakan Algoritma Regresi Linear di Nolbas SVNR - Muhammad Fadhilah; Martanto Martanto; Irfan Ali (Masoem University, 2023)
Nolbas svnr is a business engaged in the clothing industry which refers more to t-shirt screen printing. This business carries out its activities based on customer orders received through orders from individuals, shops, and schools. With the many types of screen printing that are made, the number of orders received and executed by Nolbas Svnr increases. Screen printing production at Nolbas Svnr is always changing every year. The main objective of this research is to obtain a predictive model for the amount of screen printing production using the Linear Regression method based on the number of orders obtained each year. The results that can be obtained in research can help for the supply of raw materials, the amount of raw materials, paint and so on. This study uses the linear regression method to process sales data using attributes such as year, customer name, price of goods, price of materials and the number of orders. of 0.5601. The results of the constant values ??and regression coefficients are used to predict the amount of screen printing production in 2023 at Zerobas SVNR and the predicted value is 3391. Evaluation of the multiple linear regression model shows an MAE value of 3.7247, an MSE value of 17.8633 and an R2 score of 87% .